Analysis of reproductive patterns of fishes from three Large Marine Ecosystems - Trindade-Santos, Isaac; Freire, Kátia de Meirelles Felizola (Frontiers in Marine Science, 2015)
Fish reproductive biology plays an important role for fishery management, especially in developing countries. The aim of this study was to compile all available information and analyze reproduction patterns of marine fishes in three Large Marine Ecosystems (LMEs): North, East, and South Brazil Shelves. We tested the hypothesis that the onset and duration of spawning season differ among these three LMEs; compared the ratio between length at first maturity and asymptotic length with the global trend observed; analyzed sex ratios; and tested whether females allocate more energy into reproduction than males. The following data were compiled from published sources and ‘grey’ literature: sex ratio, spawning season, gonadosomatic indices (GSI), and length at first maturity (Lm). The reproductive load was estimated as Lm/L∞. The median extension of the spawning season in the North, East, and South Brazil Shelves were 6.5, 6.0 and 5.0 months, respectively, with higher frequency during austral summer in South Brazil. Marine fishes from these three LMEs can be grouped in summer and non-summer spawners. About ninety six percent of the cases the reproductive load was between 0.3 and 0.8, which is slightly shifted toward smaller values, compared with the global range of 0.4-0.9. Gonadosomatic indices for females were higher. Contrary to some expectations, there is seasonality in the reproduction of tropical fishes. However, seasonality is stronger in southern populations. Size at first maturity is not efficiently used as a tool for fisheries management in the ecosystems analyzed.